Relationship between symptoms and quality of life in fecal incontinence. Issue 3 (2nd November 2017) - Bedard, K.; Heymen, S.; Palsson, O. S.; Bharucha, A. E.; Whitehead, W. E.
Abstract: Background: Most measures of fecal incontinence (FI) severity assess the frequency of solid and liquid FI, but may incorporate other features. We compared two scales—the Fecal Incontinence Severity Score (FISS) and Fecal Incontinence Severity Index (FISI)—to determine which questionnaire and which individual questions predict FI Quality of Life (FIQOL). Methods: A national sample of American adults completed a health questionnaire, and 234 with monthly FI were selected. Participants completed assessments of FI severity, FIQOL, and somatization. Stepwise linear regression models evaluated whether FISS and FISI total scores, or individual items on the FISS and FISI predicted FIQOL after adjusting for gender, age, income, and somatization (Brief Symptom Inventory‐18). Key Results: Reliable responses were provided by 186. Age was 49 years, and 52% were women. The mean FISS score was 8.4 (95% confidence interval [CI] 8.0‐8.9, 13 questions) and mean FISI was 29.9 (95% CI 27.4‐32.4, 62 questions), indicating moderate FI severity. The mean FIQOL was 2.6 (95% CI 2.4‐2.7, 5 questions). Lower income, greater somatization, and total FISS and FISI scores explained 69% of FIQOL; and total FISS and FISI scores were independent predictors. On the FISS, frequency, amount, and urgency to defecate were independently associated with FIQOL. After adding somatization, all but amount remained significant. For the FISI scale, solid and liquid FI and gas were significant predictors, but adjusting for somatization excluded solid FI. Conclusions and Inferences: Five variables independently explained FIQOL: overall frequency of FI, frequency of liquid and gas leakage, urgency, and somatization. Abstract : We compared two commonly used scales of the severity of fecal incontinence to determine which is the best predictor of disease‐specific quality of life (Rockwood Fecal Incontinence Quality of Life Scale). The two scales are the Fecal Incontinence Severity Scale and the Fecal Incontinence Severity Index.